2017
DOI: 10.1097/mao.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Time to Emergence of Auditory Skills After Cochlear Implantation of Children With Charge Syndrome

Abstract: Auditory skills may develop slowly in children with CHARGE syndrome who receive a CI but most can achieve at least improved detection. In our series, half acquired some speech perception ability. Cochlear nerve deficiency is frequent, but should not be a contraindication to implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…Peters et al (2010) found 56% of surgeons believed additional disability to be a contraindication to bilateral implantation in children. More recent studies neither support nor refute this hypothesis: some show fewer children with additional needs receiving bilateral devices relative to unilateral devices (Eshraghi et al 2015; Young et al 2017; Datta et al 2020) and others show no difference (Nasralla et al 2018; Mesallam et al 2019). Nevertheless, data from the present study suggest children with an additional disability had an increased likelihood of having one CI, which may account for lower daily device use in unilateral users.…”
Section: Discussionmentioning
confidence: 92%
“…Peters et al (2010) found 56% of surgeons believed additional disability to be a contraindication to bilateral implantation in children. More recent studies neither support nor refute this hypothesis: some show fewer children with additional needs receiving bilateral devices relative to unilateral devices (Eshraghi et al 2015; Young et al 2017; Datta et al 2020) and others show no difference (Nasralla et al 2018; Mesallam et al 2019). Nevertheless, data from the present study suggest children with an additional disability had an increased likelihood of having one CI, which may account for lower daily device use in unilateral users.…”
Section: Discussionmentioning
confidence: 92%
“…However, emergence of measurable open-set speech perception occurred on average 4.5 years post-CI, far later than usual. Delayed emergence of skills has been reported in implanted children with other complicating conditions (18)(19)(20). In addition, the majority of nonmedically complex children who receive a CI before 3 years of age develop measurable open-set speech perception, varying from 93.5% for those implanted under 1 year of age to 84.7% for those implanted after 2 years (21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variety of techniques proposed for cochlear implantation in CHARGE syndrome, considerable variability in outcomes exists. One recent study found that after cochlear implantation in 12 children with CHARGE, two saw minimal benefit, four demonstrated improved sound detection, three developed closed set speech perception, and three had open set speech perception . This variability likely reflects the large range of otologic abnormalities that can exist in CHARGE syndrome, such as the degree of cochlear hypoplasia, the diameter of the internal auditory canal to accommodate varying numbers of cochlear neurons, and presence of SGNs.…”
Section: Discussionmentioning
confidence: 99%